Functional specialisation and working conditions in Europe - Roman Stöllinger; Sandra M. Leitner; Zuzana Zavarska (The Vienna Institute for International Economic Studies (wiiw), 2023)
Specialisation in value-chain functions is one of the new phenomena introduced by global value chains (GVCs). This report investigates the effects of functional specialisation on labour markets in fabrication and R&D activities as the two polar cases of value-chain functions, whereby the former is associated with factory economies, while the latter is characteristic of headquarter economies. More precisely, a metric similar to revealed comparative advantage is used to study the effect of relative functional specialisation on wages and non-wage working conditions. In line with the GVC literature emphasising power relations and organisational aspects of production networks, we are able to identify differentiated effects for functional specialisation patterns on wages in EU member states at the industry level across time. While relative functional specialisation in fabrication tends to hold back wages, functional specialisation in R&D has a positive effect on wage progression, controlling for labour productivity, GVC participation and numerous labour supply- and labour demand-side factors. The use of a constructed 'sharp' instrument allows giving these results a causal interpretation. Conversely, both functional specialisation measures are found to improve some non-wage working conditions, namely workers' physical environment and their work intensity, which is evidence against a potential 'race to the bottom' effect of functional specialisation along GVCs. The effect is stronger for relative specialisation in fabrication than for relative specialisation in R&D.
Keywords: F15; F21; F23; F63; J31; 330; Functional specialisation; wages; non-wage working conditions; global value chains